Relationship between the transcriptional activity of СT-genes and survival in colorectal cancer patients - D. S. Kutilin; O. I. Kit (Сибирский онкологический журнал)
Introduction. High incidence and mortality rates of colorectal cancer indicate an urgent need for the use of new highly specific diagnostic and prognostic molecular markers. In this aspect, cancer testis antigens (CTA s) are of particular interest.The aim of the study was to analyze the relationship between the transcriptional activity of CTA s and survival in colorectal cancer patients with metastases (T1–4N1–2M1–2) and without metastases (T1–3N0M0).Results. The relative expression of 16 genetic loci (MAGE-A1, MAGE-A2, MAGE-A3, MAGE-A4, MAGE-B1, MAGE-B2, GAGE-1, GAGE-3, GAGE-4, MAGE-C1, BAGE, XAGE3, NYESO1, SSX2, SCP1 and PRAME1) was determined by real-time PC R. In colorectal cancer patients having no metastases, the expression of SSX2 and PRAME1 genes was significantly higher and the expression of BAGE was significantly lower in colon tumor tissue than in normal tissue (p<0.05). In colorectal cancer patient with metastases, the expression of GAGE1, SCP1 and PRAME1 genes was significantly higher and the expression of MAGEA2, MAGEB1, MAGEB2, GAGE4 and NY-ESO1 genes was significantly lower in colon tumor tissue than in normal tissue (p<0.05). The expression of the GAGE1, BAGE, SSX2, MAGEA2, SCP1 and MAGEB1 genes was found to have a significant impact on the overall survival and the development of distant metastasis (p<0.05).Conclusion. The data obtained are the basis for the formation of a panel of effective immunotherapeutic targets and prognostic markers for colorectal cancer patients with and without metastases.